Pengembangan Critical Thinking Dalam Peningkatan Mutu Pendidikan di Indonesia - Atris Yuliarti Mulyani (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2022)
Critical thinking is the ability to think that exists in students. This ability helps students face every problem using scientific thinking. Critical thinking consists of the words "thinking" and "critical." According to the KBBI, thinking is using the mind to consider and decide something, while critical thinking is interpreted as not being easy to believe, always trying to find problems, and sharpness in analyzing. Many expert opinions explain the meaning of critical thinking. However, the notion of critical thinking can be concluded as the ability to think of humans by using a focused and deep understanding to find a definite bright spot. The use of critical thinking can solve problems in life, including problems in education in Indonesia. This is because critical thinking has the characteristics of solving problems with systematic conclusions and correct arguments. Educational problems can be resolved by providing solutions based on the results of critical thinking. If the problem of education is resolved by taking several things into account, the quality of education will slowly improve.